Book review: “Closing Space: Democracy and Human Rights Support Under Fire” by Thomas Carothers and Saskia Brechenmacher - Stuenkel, Oliver (Faculdade de Filosofia e Ciências, 2014)
International support for democracy and human rights faces a serious challenge”, Thomas Carothers and Saskia Brechenmacher argue in a report published by the Carnegie Endowment for International Peace. According to them, a growing number of governments are erecting legal and logistical barriers to democracy and rights programs, “publicly vilifying international aid groups and their local partners, and harassing such groups or expelling them altogether.”